PENERAPAN MODEL PROBLEM-BASED LEARNING DENGAN PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII - Arin Dwi Anjani; Eka Senjayawati; Onis Suciati (IKIP Siliwangi, 2023)
This research is a classroom action research that aims to determine the motivation to learn mathematics in class VII students of SMP Negeri 1 Margaasih. This study applies the problem-Based Learning model using the STAD (Student Teams Achievement Division) Cooperative type. The Kemmis & Tanggart research model was used three cycles. The subjects of this study were student of class VII-E in group C with 10 student. The data obtained in this study through a student learning motivation questionnaire. Questionnaire data on students’ learning motivation was analyzed in the form of percentage. The results of the research were obtained for three cycles as follows: cycle 1 with a percentage of 77.2%, cycle 2 with a percentage of 85.4%, and cycle 3 with a percentage of 90%. The conclusion based on this research is that the use of the Problem Based Learning approach using the STAD (Student Teams Achievement Division) cooperative is effective in increasing the motivation to learn mathematics in class VII students at SMP Negeri 1 Margaasih.